PLANKTON AND WATER QUALITY ANALYSIS ON THE PRODUCTION PERFORMANCE OF WHITE SHRIMP (LITOPENAEUS VANNAMEI) - Jatayu, Diklawati; Nisa, Andina Chairun; Amelia, Tia (Universitas Mataram, 2025)
The abundance, diversity, and dominance of phytoplankton affect water quality which can directly affect the success of cultivation. This study was conducted to analyze the diversity of species and dynamics of plankton abundance in shrimp (Litopenaeus vannamei) cultivation in intensive white shrimp ponds in Sumenep, Madura. Observations of plankton, water quality, and white shrimp production were carried out in four ponds for ± 2 months. Data analysis was carried out on water quality data, plankton community structure and white shrimp cultivation production performance. Water quality data and production performance were analyzed descriptively qualitatively while plankton community structure data (biological index) were analyzed descriptively quantitatively. The results of the identification of zooplankton types obtained from the samples amounted to 2 classes, consisting of 7 genera of protozoa and 1 genus of Rotifera. The most abundant zooplankton is the Protozoa Class with 7 genera. The highest plankton abundance is from the Genus Chlorophyta (74.67% ± 4.49%), then the second highest is from the Genus Cyanophyta (18.01% ± 3.40%). The results of the diversity index analysis (H’) in pond 5 were 2.246 indicating high diversity, while ponds 6,7, and 8 showed moderate diversity. The uniformity index showed that pond 5 had a high uniformity index with a value of 0.66 while ponds 6,7, and 8 had moderate uniformity. The dominance index analysis showed that in pond 5 with a value of 0.978 there were dominant species, while ponds 6, 7, 8 did not have dominant species. Water quality observations showed that there were nitrate parameters that exceeded the optimum standard. The performance of white shrimp cultivation showed better results in pond 5 indicated by ADG of 0.35 g/day, ABW 14.9 g, FCR 1.6 and SR 71%.